MicroRNA-138-5p Suppresses Non-small Cell Lung Cancer Cells by Targeting PD-L1/PD-1 to Regulate Tumor Microenvironment - Song, Nannan; Li, Peng; Song, Pingping; Li, Yintao; Zhou, Shuping; Su, Qinghong; Li, Xiaofan; Yu, Yong; Li, Pengfei; Feng, Meng; Zhang, Min; Lin, Wei (Frontiers in Cell and Developmental Biology, 2020)
Non-small cell lung cancer (NSCLC) is still challenging for treatment owing to immune tolerance and evasion. MicroRNA-138 (miR-138) not only acts as a tumor suppressor to inhibit tumor cell proliferation and migration but also regulates immune response. The regulatory mechanism of miR-138 in NSCLC remains not very clear. Herein, we demonstrated that miR-138-5p treatment decreased the growth of tumor cells and increased the number of tumor-infiltrated DCs. miR-138-5p not only down-regulated the expression of cyclin D3 (CCND3), CCD20, Ki67 and MCM in A549/3LL cells, but also regulated the maturation of DCs in A549-bearing nude mice and the 3LL-bearing C57BL/6 mouse model, and DCs’ capability to enhance T cells to kill tumor cells. Furthermore, miR-138-5p was found to target PD-L1 to down-regulate PD-L1 on tumor cells to reduce the expression of Ki67 and MCM in tumor cells and decrease the tolerance effect on DCs. miR-138-5p also directly down-regulates the expression of PD-L1 and PD-1 on DCs and T cells. Similar results were obtained from isolated human non-small cell lung cancer (NSCLC) cells and DCs. Thus, miR-138-5p inhibits tumor growth and activates the immune system by down-regulating PD-1/PD-L1 and it is a promising therapeutic target for NSCLC.